1987
DOI: 10.1039/c39870001891
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylation of methanol at unusually low temperature and pressure with cis-RhCl(CO)2Ph2P(CH2)2P(O)Ph2

Abstract: c ~s -R ~C I ( C O ) ~P ~~P ( C H ~) ~P ( O ) P ~~, the only species observed during catalysis, formed from cis-hhCI(CO)Ph2P(CH2P(~)Ph2 and CO, is the sole active species observed during catalytic studies and results in the carbonylation of methanol with catal st turnover frequencies approaching 400 h-1 at 80°C and 50 psig CO; the crystal structure of the analogue cis-hCI(CO)Ph2PCH2P(0)Ph2 is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1
6

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 0 publications
2
78
1
6
Order By: Relevance
“…During 60 min of reaction time (Table 2), 54.54, 65.08 and 53.70% conversions of methanol were obtained with corresponding turn over number (TON) 812, 1004 and 828 for the complexes 1a, 1b and 1c, respectively, which further increases with the increase in reaction time. In general, for a particular reaction time and conditions, complexes 1 show higher catalytic activity over the wellknown catalyst precursor [Rh(CO) 2 …”
Section: Carbonylation Of Methanolmentioning
confidence: 99%
See 3 more Smart Citations
“…During 60 min of reaction time (Table 2), 54.54, 65.08 and 53.70% conversions of methanol were obtained with corresponding turn over number (TON) 812, 1004 and 828 for the complexes 1a, 1b and 1c, respectively, which further increases with the increase in reaction time. In general, for a particular reaction time and conditions, complexes 1 show higher catalytic activity over the wellknown catalyst precursor [Rh(CO) 2 …”
Section: Carbonylation Of Methanolmentioning
confidence: 99%
“…The rhodium dimer, [Rh(CO) 2 Cl] 2 , reacts with two molar equivalent of the ligands a-c to give the complexes of the type [Rh(CO) 2 ClL](1), where L = 2-aminophenol (a), 3-aminophenol (b) and 4-aminophenol (c) (Scheme 1). Elemental analyses of the complexes were determined and the results match well with the calculated values.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Transition metal complexes of these ligands have attracted much attention due to their versatile coordination chemistry and their application in catalysis [3][4][5]. Grim et al [6] have reported complexes of Ph 2 PCH 2 P(O)Ph 2 and Ph 2 P(O)CH(Pr)PPh 2 (Pr = n-propyl) with HgX 2 (X = Cl, Br).…”
Section: Introductionmentioning
confidence: 99%